Relationship between the Methane Production and the CNCPS Carbohydrate Fractions of Rations with Various Concentrate/roughage Ratios Evaluated Using In vitro Incubation Technique - Dong, Ruilan (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
The objective of the trial was to study the relationship between the methane (CH(4)) production and the Cornell Net Carbohydrate and Protein System (CNCPS) carbohydrate fractions of feeds for cattle and the suitability of CNCPS carbohydrate fractions as the dietary variables in modeling the CH(4) production in rumen fermentation. Forty-five rations for cattle with the concentrate/roughage ratios of 10:90, 20:80, 30:70, 40:60, and 50:50 were formulated as feed samples. The Menke and Steingass’s gas test was used for the measurement of CH(4) production. The feed samples were incubated for 48 h and the CH(4) production was analyzed using gas chromatography. Statistical analysis indicated that the CH(4) production (mL) was closely correlated with the CNCPS carbohydrate fractions (g), i.e. CA (sugars); CB(1) (starch and pectin); CB(2) (available cell wall) in a multiple linear pattern: CH(4) = (89.16±14.93) CA+ (124.10±13.90) CB(1)+(30.58±11.72) CB(2)+(3.28±7.19), R(2) = 0.81, p<0.0001, n = 45. Validation of the model using 10 rations indicated that the CH(4) production of the rations for cattle could accurately be predicted based on the CNCPS carbohydrate fractions. The trial indicated that the CNCPS carbohydrate fractions CA, CB(1) and CB(2) were suitable dietary variables for predicting the CH(4) production in rumen fermentation in vitro.